Proceedings of the 19th ACM Workshop on Hot Topics in Networks 2020
DOI: 10.1145/3422604.3425923
|View full text |Cite
|
Sign up to set email alerts
|

Remote Memory Calls

Abstract: In this paper we propose an extension to RDMA, called Remote Memory Calls (RMCs), that allows applications to install a customized set of 1-sided RDMA operations. We then explain how RMCs can be implemented on the forthcoming generation of SmartNICs and discuss the resulting tradeoffs between RMCs, 1-sided RDMA operations, and 2-sided RDMA operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…An RDMA call is ultimately a DMA operation from the server's NIC to its main memory. Programmable NICs can enable new RDMA primitives [2,45], even requiring multiple DMA calls per-packet [2]. Similarly, this can open new opportunities to rethink how direct telemetry access is implemented.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An RDMA call is ultimately a DMA operation from the server's NIC to its main memory. Programmable NICs can enable new RDMA primitives [2,45], even requiring multiple DMA calls per-packet [2]. Similarly, this can open new opportunities to rethink how direct telemetry access is implemented.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative approach is letting end-hosts assist in network-wide telemetry [22,46], which unfortunately requires significant investments and infrastructure changes. Switch-generated RDMA calls Recent work has shown that programmable switches can perform RDMA calls [33], and that programmable network cards are capable of expanding upon RDMA with new and customized primitives [2]. Especially FPGA network cards show great promise for highspeed custom RDMA [39,45].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…RDMA verbs cannot support the management of complex data structures while guaranteeing no conflicts or race conditions in the presence of multiple clients accessing the same memory region. Following the spirit of past works that explored ways to extend RDMA [3], the translator can be used as an enabler for custom RDMA operations available at reporters. The translator is in charge of receiving telemetry data, aggregating it, and performing standard RDMA calls to the associated collector.…”
Section: Direct Telemetry Accessmentioning
confidence: 99%
“…In a non-congested scenario, the translator generates appropriate RDMA calls upon the reception of DTA traffic. In case of congestion, it either drops low-priority data or re-routes critical reports to its local CPU for temporary storage 3 . It further informs reporters of the congestion to limit additional non-critical telemetry data.…”
Section: Dta Translatormentioning
confidence: 99%